Guide wire placement for fifth metatarsal intra-medullary screw fixation: A technical tip. (August 2016) - Grice, John; Calder, James
Highlights: It can be difficult to pass a guide wire across a partially occluded medullary canal. A blunt angled guide wire can facilitate crossing the callus. Good guidewire position will reduce surgical complications. Abstract: Treatment of fifth metatarsal fractures in elite athletes or delayed/non unions often requires operative fixation. However, this can cause technical difficulties and we present an operative tip to avoid complications is presented.